Analisis Implementasi Pengelolaan Lingkungan Laut untuk Mendukung SDGs Desa: Studi Kasus di Desa Kalibaru, Jakarta Utara - hakim, Muhammad Lukman Hakim; Hanif, Nita Aribah (Journal of Politics and Democracy, 2024)
This study aims to analyze the implementation of marine environmental management in Kalibaru Village and its contribution to the achievement of the Sustainable Development Goals (SDGs), particularly Goal 14 on the conservation of marine ecosystems. The research focuses on evaluating local policies and identifying key challenges, including limited funding, technical capacity, low community awareness, and inadequate technological support. The study employed a qualitative method with a case study approach. Primary data were collected through interviews with village officials, sub-district government representatives, fishermen, and community leaders, as well as field observations of the local marine environment. Data were analyzed using thematic coding techniques to identify significant patterns in management practices. The findings reveal that although policies such as waste management and fisheries regulation exist, their implementation remains weak. High levels of marine pollution from plastic and industrial waste, coupled with low public awareness, have resulted in poor environmental conditions. Nevertheless, there has been progress in increasing environmental awareness, improving stakeholder coordination, and stabilizing fish stocks, which has positively impacted fishermen’s livelihoods. In conclusion, marine environmental management in Kalibaru Village has shown some progress but remains limited. Strengthening regulations, enhancing technical capacity, and providing sustainable funding and technology are essential to make management more effective and contribute significantly to the achievement of the Village SDGs